Analysis and optimization of the performance for the ground source heat pump system with the middle-deep U-type well. (25th January 2023) - Zhang, Wenke; Wang, Kexun; Guan, Chunmin; Yao, Haiqing; Li, Wenjing; Gao, Yuxue; Cui, Ping
Highlights: The structure characteristics and the energy equations are revealed. Investigate the hourly heat load of the buildings for the heating season. Establish the models of equipment. The COP can be optimally increased by more than 25%. Analyze significant factors influencing the COP of heat pump unit. Abstract: "Extract heat without water extraction" technology in the middle-deep geothermal energy utilization has attracted increasing attentions, and the U-type well is a significant ground heat exchanger (GHE) of ground source heat pump (GSHP) system. This paper describes the structural characteristics and establishes the energy equations for the U-type well, and summarizes both the initial and the boundary conditions of the heat transfer process. Afterwards, a certain building with a GSHP system is selected, and the hourly heat load is investigated via the TRNSYS simulation platform; the components of the system are discussed. Next, the models of the heat pump unit, the water pump and other elements are established to lay a firm foundation for the optimization of the system, and therefore the optimization of the research route are conducted. Finally, the parameters or cases influencing the performance of the heat pump unit are analyzed, and the optimized and the existing results are compared to demonstrate the significance of optimization; the COP can be increased by more than 25% while the optimized measures are employed. The research results of this paper can facilitate the development of the GSHP systems with the U-type well, and promote the popularization and application of the middle-deep geothermal energy.